1980
DOI: 10.1111/j.1365-2842.1980.tb00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of symptoms of functional disturbances of the masticatory system in Swedish men

Abstract: Subjective and clinical symptoms of mandibular dysfunction and cuspal interferences were studied in 389 Swedish men (median age 32 years). Impaired chewing function was noted in about 10%, different types of parafunction in 26%, frequent headaches in 5%, TMJ or muscle pain in 3% and difficulties in mouth opening in 10% of the men. Locking or luxation of the mandible was the most prevalent clinical symptom (24%), followed by reduced movement capacity and deviation on opening of the mandible, TMJ-sounds and musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
14

Year Published

1982
1982
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(53 citation statements)
references
References 19 publications
3
35
1
14
Order By: Relevance
“…Molin et al (1976) studied a general population of men {n = 253) and found that none of the individual oeelusal variables pooled to form the variable oeelusal disturbances, differed signifieantly in frequeney between the groups with and without clinical dysfunction. Ingervall et al (1980) found that grouping of interferences did not reveal any closer correlation with symptoms than the individual types of interferences. Finally, Helkimo (1974a, b) created an oeelusal index to pool functional and structural aspects of occlusion and compared them to mandibular dysfunction.…”
Section: Occlusionmentioning
confidence: 80%
“…Molin et al (1976) studied a general population of men {n = 253) and found that none of the individual oeelusal variables pooled to form the variable oeelusal disturbances, differed signifieantly in frequeney between the groups with and without clinical dysfunction. Ingervall et al (1980) found that grouping of interferences did not reveal any closer correlation with symptoms than the individual types of interferences. Finally, Helkimo (1974a, b) created an oeelusal index to pool functional and structural aspects of occlusion and compared them to mandibular dysfunction.…”
Section: Occlusionmentioning
confidence: 80%
“…The explanatory value of occlusal interferences for the variation of dysfunction in these studies was small, however (24,25,(29)(30)(31). The inconsistent results of previous studies related to the influence of occlusal factors on function and dysfunction of the masticatory system have been reviewed earlier (32)(33)(34).…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, in their study six out of eight subjects with a clinical dysfunction score had a reduced score after occlusal adjustment. Epidemiological studies have also demonstrated correlations between signs and symptoms of mandibular dysfunction and balancing-side interferences (11,12) and interferences in RP (13).…”
Section: Experimental Clinical Study; Interferences; Mandibular Dysfumentioning
confidence: 95%